INFLUENCE OF PROMOTION MIX TOWARDS PURCHASE INTENTION OF MAJESTIC ORGANIZER - Limawan, Alvin Nathanael; Aprianingsih, Atik (Journal of Business and Management, 2018)
Abstract.Economy Creative (Ekraf) is one of the expected sector that can be a new power of national economy in the future. Start-up business in Economy Creative Industry have to possess high creativity and can create uniqueness in their products or services like in event organizer Industry. However, as a start up business industry face similar problem commonly which is marketing problem. Majestic Organizer is still a start up business and still growing in Bandung. Majestic Organizer have a big market that never run out, because most of people will seventeenth years old which means new every year. But Majestic Organizer not yet maximizing their pontetial market and still stuck in sales. Since in event organizer industry is a free industry for everyone can join to this industry so Majestic Organizer should have a good marketing communication to compete and gain market share. From marketing mix, promotion is the part of marketing mix that can be used to raise awareness about the company. Moreover the purpose of this research is to analyze the relationship of promotional mix with purchase intention for Majestic Organizer. The data for this research was collected using quatitative approach through online questionnaire to 201 respondents. The data is analyzed using multiple linear regression to see the relationship between promotional mix and purchase intention. The result shows that promotional mix do have a positive significant influence towards purchase intention.Keywords: Advertising, Majestic Event Organizer, Personal Selling, Promotional Mix, Purchase Intention